Carbon pricing of basic materials: Incentives and risks for the value chain and consumers - Jan Stede; Stefan Pauliuk; Gilang Hardadi; Karsten Neuhoff (Ecological Economics, 2021)
Different options for a reform of the EU Emissions Trading System are discussed to ensure carbon price incentives for mitigation options in the basic materials sector, while minimizing carbon leakage risks. This paper quantifies carbon leakage risks, distributional implications, and additional revenues associated with an import-only border carbon adjustment (BCA), a symmetric (import and export) BCA, and an excise for embodied emissions at a fixed benchmark level in combination with continued free allocation. We estimate the product-level carbon intensities for 4400 commodity groups, compute maximal implied price changes due to full carbon pricing, and calculate cost increases relative to gross value added to assess the scale of carbon leakage risks. We show, first, that around 10% of EU exports and 5% of all domestic manufacturing sales meet the criteria for carbon leakage risk under an incomplete BCA at a carbon price of 30 EUR/t. Second, the distributional implications of consistent carbon pricing of basic materials are small and progressive. Finally, an excise could generate revenues of around 20 billion euros that may be used towards climate action. Our results on potential carbon leakage risks and their mitigation can inform responsible policy making to shape the EU pathway towards climate neutrality.
Keywords: F18; C67; 330; Emissions trading; Border carbon adjustment (BCA); Excise duty; Carbon intensity; Carbon leakage; Distributional effects; Fiscal revenues